DNA BARCODING OF FISH SPECIES FROM THE MEDITERRANEAN COAST OF ISRAEL - SHIRAK, A.; DOR, LIOR; SEROUSSI, E.; RON, M.; HULATA, G.; GOLANI, D. (Mediterranean Marine Science, 2016)
Accurately-classified genomic data in the Barcode of Life Data System (BOLD) database is vital to the protection and conservation of marine biodiversity in the Mediterranean Sea. The taxonomic classifications of 468 fish of 50 Mediterranean species were analyzed using the BOLD Identifier tool for variation in the cytochrome oxidase subunit I (COI) mitochondrial gene. Within species, nucleotide maximum composite likelihood was low with a mean of 0.0044±0.0008. Three presumptive species had significantly higher values e.g., Arnoglossus spp. (0.07), Torquigener flavimaculosus (0.013) and Boops boops (0.028). However, samples of Arnoglossus species were sub-classified into two groups that were finally identified as two different species e.g., Arnoglossus laterna and Arnoglossus thori. For the different species, BLAST searches against the BOLD database using our DNA barcoding data as the query sequences designated the most similar targets into groups. For each analyzed species, the similarity of the first and second threshold groups ranged from 95 to 99% and from 83 to 98%, respectively. Sequence based classification for the first threshold group was concordant with morphology-based identification. However, for 34 analyzed species (68%) overlaps of species between the two threshold groups hampered classification. Tree-based phylogeny analysis detected more than one cluster in the first threshold group for 22 out of 50 species, representing genetic subgroups and geographic origins. There was a tendency for higher conservation and lower number of clusters in the Lessepsian (Red Sea) migrant versus indigenous species.